Creación de una lista de chequeo para el mejoramiento del proceso de admisión de historias clínicas de los servicios ambulatorios de la clínica Central o.h.l ltda. Montería - Córdoba (2022)
This report aims to publicize the subject matter carried out during the business practice carried out at the Clinic Central OHL of Monteria. The place where the practices were carried out was the admission area for medical records from the outpatient area destined for the billing and filing area. The research work consisted of monitoring these medical records as a pre-audit in order to reduce reprocessing that may arise due to poor diligence, lack of documents and/or errors at the time of preparation. The analysis of this process was carried out through the DOFA matrix tool. With which he hopes to reduce audit times. In the study it was found that there are medical records that show deterioration when they are in boxes, they were not signed by the doctors or with empty fields. It was recommended that the healthcare staff of the institution that fills out the clinical histories, do so clearly, in legible handwriting, without crossing out, emendations and, if possible, avoiding acronyms, and have a complete medical history, with all parts of the same